2021
DOI: 10.3389/fphar.2021.720224
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Fat and High-Fat/High-Sucrose Diet-Induced Obesity on PVAT Modulation of Vascular Function in Male and Female Mice

Abstract: Increased adiposity in perivascular adipose tissue (PVAT) has been related to vascular dysfunction. High-fat (HF) diet-induced obesity models are often used to analyze the translational impact of obesity, but differences in sex and Western diet type complicate comparisons between studies. The role of PVAT was investigated in small mesenteric arteries (SMAs) of male and female mice fed a HF or a HF plus high-sucrose (HF + HS) diet for 3 or 5 months and compared them to age/sex-matched mice fed a chow diet. Vasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…The authors concluded that the potential mechanisms underlying these effects may be related to the different adipocyte species that comprise tPVAT and aPVAT [131]. Victorio et al reported that the effect of HF and HS diets on PVAT differs depending on sex [132]. The anti-contractile effect of PVAT was measured by comparing the phenylephrine-induced contraction in mesenteric arteries after 3 and 5 months of HF or HF+HS diet among male and female mice.…”
Section: The Potential Influence Of Diet On Pvat-derived Factors Among Obese Patientsmentioning
confidence: 99%
“…The authors concluded that the potential mechanisms underlying these effects may be related to the different adipocyte species that comprise tPVAT and aPVAT [131]. Victorio et al reported that the effect of HF and HS diets on PVAT differs depending on sex [132]. The anti-contractile effect of PVAT was measured by comparing the phenylephrine-induced contraction in mesenteric arteries after 3 and 5 months of HF or HF+HS diet among male and female mice.…”
Section: The Potential Influence Of Diet On Pvat-derived Factors Among Obese Patientsmentioning
confidence: 99%
“…In contrast to our study, a beneficial PVAT function (anticontractile activity) was shown to be retained in the aortas of male Dahl salt-sensitive rats that were fed a high-fat diet for 24 weeks (from 3 weeks), but not in females [26]. Similarly to the study into Dahl salt-sensitive rats, the anti-contractile PVAT function was found to be impaired for 3-5 months in the superior mesenteric arteries of female C57Bl/6 mice, following administration of a highfat or high-fat plus high-sucrose diet from 2 months of age, but was preserved in males [40]. However, sex-related differences have often been either unreported or not considered during experimental design in preclinical research, so we cautiously interpret our results as evidence that PVAT function varies by sex.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…PVAT has been found to have no effect on endothelium-dependent methacholine-induced relaxation in the aortas of obese female Zucker rats [23], although it has been shown to impair relaxation in males [24]. Through the administration of a high-fat diet, PVAT anti-contractile effects have been shown to be impaired in the superior mesenteric arteries of female C57Bl6 mice [25], and in the aortas of female Dahl salt-sensitive rats [26], but not in the arteries of corresponding males. In contrast, PVAT-assisted stress relaxations in the aortas of Dahl salt-sensitive rats did not differ between sexes [27].…”
Section: Introductionmentioning
confidence: 99%
“…The obesity has also been demonstrated to alter the perivascular adipose tissue (PVAT) ( 58 , 59 ). PVAT presents morphological characteristics that vary according to the vascular bed, resembling WAT in mesenteric arteries and abdominal aorta or BAT/beige in thoracic aorta ( 60 62 ).…”
Section: Changes In Adipose Tissue Depots In Obesity: a Role For Er S...mentioning
confidence: 99%